Holiday Heartbreak - Russell, Rachel Renee (UK, 2013)
I have to accept that maybe Brandon's not into me... 1. He agreed to hang out at Crazy Burger then rudely cancelled at the last minute. 2. He texted an apology instead of telling me in person. 3. He's probably too embarrassed to be seen with a Dork! Brandon has finally asked Nikki out, but now he's acting weirdly. Does he like her? The sweetheart dance - where girls ask guys - might be the perfect opportunity to find out! But is Nikki brave enough to ask?...
Keywords: Friendship; Juvenile Fiction